Characterization of biosurfactants as insecticidal metabolites produced by Bacillus subtilis Y9 - Yang, Si Young; Lim, Da Jung; Noh, Mi Young; Kim, Jin Cheol; Kim, Young Cheol; Kim, In Seon (Entomological research, 2017)
Biosurfactants have been used for crop protection in integrated pest management programs, as they are generally biodegradable and environmentally friendly. While screening for insecticidal bacteria against green peach aphid, Myzus persicae , we found that a Bacillus isolate, Y9, exhibited strong surface tension activity and produced insecticidal metabolites. The insecticidal metabolites with surface tension activity were extracted from the cell‐free supernatant of Y9 and subjected to repetitive column chromatography and preparative high performance liquid chromatography (HPLC). Based on data from instrumental analyses, the metabolites were identified as surfactin isomers consisting of C 14 [Leu 7 ], C 14 [Val 7 ] and C 15 [Leu 7 ]. The isomers with leucine showed higher insecticidal activity than the isomers with valine. Y9 was capable of producing biosurfactants as insecticidal metabolites against M. persicae , and showed potential for use as a biocontrol agent in an integrated pest management program.